PEMBUATAN WEBSITE JEKS TOURISM SEBAGAI MEDIA INFORMASI AGROWISATA JERUK KEPROK DI KABUPATEN KEPULAUAN SELAYAR - Ilham Ahmad; Andryanto A; Adilham Adilham; Karma Karma (LPPM Universitas Bina Bangsa, 2023)
The Regency of Kepulauan Selayar holds significant potential in orange agrotourism, but the available information is still limited. Therefore, the implementation of this community service aims to create a website named